Effects of glyphosate on the movement of assimilates of two Lolium perenne L. populations with differential herbicide sensitivity - Yanniccari, Marcos Ezequiel (2012)
Glyphosate applications trigger the depletion of aromatic amino acid pools and the decrease of photosynthesis that results in changes in carbon metabolism. The aim of this work was to determine the effect of glyphosate on the export of 14C from 14C-glucose to the main sinks, by comparing a glyphosate-resistant Lolium perenne population with a susceptible one. Untreated plants of the two populations grown in hydroponics were labeled with 14C-glucose applied at the youngest expanded leaf at the tillering stage. Similar 14C-glucose absorption and 14C distribution patterns were recorded in both populations. In another experiment, half of the plants of each population were treated with glyphosate, whereas the other half was sprayed with water (controls). Glucose absorption did not vary under glyphosate treatment, regardless of the sensitivity of each population to the herbicide. However, the translocation of 14C and its distribution patterns were significantly affected by glyphosate within 1 day in the susceptible population. The treated susceptible plants showed 57% higher 14C retention at the labeled area than their controls. The lower 14C movement significantly affected the unexpanded leaves and the apical meristem on the labeled tiller. Moreover, the 14C released from roots was significantly decreased by glyphosate only in the susceptible plants. Glyphosate did not influence leaf absorption, translocation, or release of 14C-labeled glucose plus radiolabeled metabolites in the resistant population.